The Concept of Gender and Its Acceptability as a Category of Analysis in Economics: An Islamic Perspective - Alsagoff, Syed Redzuan; Golam Hassan, Asan Ali; Wan Abdullah, Wan Suhaimi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2021)
Changes in the understanding of gender are making it complicated to use gender as a category of analysis. Previously, it was generally accepted that gender is a binary category, comprising of male and female, based on clear biological distinction. Then came the idea that gender is a sociocultural construct. More recently, gender is said to be based on each person’s personal conception of himself or herself. These novel ideas have detached the meaning of gender from its biological foundation and have consequently made the concept of gender ambiguous and subjective, with theoretically infinite possible interpretations that can formulate an indeterminate number of genders. Such arbitrariness is unsuitable for scientific analysis. Accordingly, mainstream economists, in their aspiration to be scientific, have largely ignored these semantic developments and have continued to use the biologically defined binary categorisation of gender, presumably because of its practicality when used in economic analysis. From an Islamic perspective, economists are right to use such definition of gender, not because it is practical to do so, but because it conforms to reality and truth (ḥaqq) as revealed by religion. This article discusses these ideas as well as their history and interactions to show that from an Islamic perspective the number of genders is not indeterminate, nor is gender only practically binary, but it is really and truly binary in line with the worldview of Islam.